Introduction of hydrogen fuel cell vehicles: prospects and challenges for Malaysias transition to a low-carbon economy - Al-Amin A.Q.; Doberstein B. (Springer Verlag, 2023)
alternative energy; energy policy; fuel cell; regulatory framework; transport vehicle; Malaysia; carbon; hydrogen; air pollution; energy resource; human; Malaysia; motor vehicle; prevention and control; public opinion; sustainable development; Air Pollution; Carbon; Energy-Generating Resources; Humans; Hydrogen; Malaysia; Motor Vehicles; Public Opinion; Sustainable Development